Pengaruh Religiusitas, Literasi, dan Akuntabilitas terhadap Minat Berwakaf Tunai di Bank Syariah Indonesia dengan Tingkat Pemahaman sebagai Variabel Moderasi - Antria Susilawati; Mursyid Mursyid; Abubakar Idham Madani (Jurnal Syntax Admiration, 2024)
Cash waqf is a form of Islamic financial empowerment that has great potential in improving social welfare. However, public interest in cash waqf is still relatively low compared to traditional waqf. This study aims to analyze the influence of religiosity, literacy, and accountability on interest in cash waqf in Bank Syariah Indonesia, with the level of understanding as a moderation variable. The method used was quantitative with a data collection technique through a questionnaire distributed to 35 customers of Bank Syariah Indonesia in Teritip Village, East Balikpapan. The data was analyzed using the Partial Least Squares (PLS) analysis technique. The results of the study show that religiosity, literacy, and accountability have a positive and significant effect on interest in cash waqf. In addition, the level of understanding moderates the relationship between religiosity, literacy, and accountability and interest in cash waqf. The conclusion of this study shows that increasing public understanding of cash waqf can increase their potential participation in the program.